KETERLIBATAN OSPA (ORGANISASI SANTRI PONDOK PESANTREN ASSHIDDIQIYYAH) DALAM MENINGKATKAN KEDISIPLINAN SANTRI DI PONDOK PESANTREN ASSHIDDIQIYYAH 3 KARAWANG - Febrianto , Rahardi; Bariah, Oyoh; Waluyo , Kasja Eki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the urgency of discipline as a key element in character development for students in Islamic boarding schools (pesantren). Despite various regulations being implemented, disciplinary violations still occur, necessitating the active involvement of student organizations as partners in the development and supervision process. In this regard, the Student Organization of Asshiddiqiyyah Islamic Boarding School (OSPA) plays a crucial role in improving student discipline through various ongoing programs and activities. This study aims to determine the role of OSPA in fostering student discipline, describe the forms of OSPA's involvement in improving student discipline, and analyze the results of OSPA's involvement at Asshiddiqiyyah 3 Putra Karawang Islamic Boarding School. This research used a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that OSPA functions as a driving force, supervisor, and role model in fostering student discipline. OSPA's involvement is realized through monitoring daily activities, implementing regulations, issuing warnings and educational sanctions, and fostering the habit of religious and learning activities. This involvement has a positive impact on increasing students' compliance with Islamic boarding school regulations, punctuality in participating in activities, and growing students' awareness and responsibility in carrying out daily obligations. Thus, OSPA plays a crucial role in creating an orderly, disciplined, and conducive Islamic boarding school environment for the development of students' characters.